Spectrums of Solvable Pantograph Differential-Operators for First Order - Z. I. Ismailov; P. Ipek (Abstract and Applied Analysis)
By using the methods of operator theory, all solvable extensions of minimal operator generated by first order pantograph-type delay differential-operator expression in the Hilbert space of vector-functions on finite interval have been considered. As a result, the exact formula for the spectrums of these extensions is presented. Applications of obtained results to the concrete models are illustrated.